A (IN ) formalização da linguagem matemática nos anos iniciais do ensino fundamental: o blog como ferramenta auxiliar - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This work within the Mathematics Education, aims to investigate the mathematical language in the early years of elementary school, and it is of great importance in school life and can sometimes even cause disruption to the student, particularly if used in controversial ways. We note the need for discussion on the language involved in this school stage, sometimes with excess formality and rigor and other impregnated of colloquial language. We seek to investigate the mathematical language used by teachers in the early years, the relationship between language and mathematics and the importance of language in teaching and learning mathematics process through theoretical and practical classroom. We used a qualitative and quantitative methodological paradigm, with data collection in a Municipal School of Anápolis, and the qualitative part was interpretative and descriptive. The data collection was done through the systematic observation of classes of seven teachers of the initial years of the School researched and of a questionnaire applied to the teachers and coordinators of the same. To broaden the didactic scope of this discussion, a blog was implemented as an educational product as a tool for continuing education. The results evidenced a strong tendency of the professors researched to use a daily language in the search to approach the contents of Mathematics to the reality of the student, mediating between the formality and informality of the mathematical language.
Keywords: Linguagem matemática; Anos iniciais; Ensino fundamental; Blog na educação; Educação Matemática; Mathematical language; Elementary school; Blog in education; Mathematics education; CIENCIAS EXATAS E DA TERRA::MATEMATICA; EDUCACAO::ENSINO-APRENDIZAGEM